(adsbygoogle = window.adsbygoogle || []).push({}); y = (sinx)^{2x}

LNy = 2xLN(sinx) + (1 over sinx)(cosx)(2x)

Answer

y' = (sinx)^{2x}[2cosx over sinx + 2xcotx]

and

y = (cosx)^{cosx}

i did it the same way as above

Answer i got was

y' = (cosx)^{cosx}[ (-sinx)(cosx) + sinx]

am i anywhere right?

**Physics Forums | Science Articles, Homework Help, Discussion**

Dismiss Notice

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Find the derivative using Logaritmic Differentiation

**Physics Forums | Science Articles, Homework Help, Discussion**